PROFIL KEMAMPUAN SPASIAL SISWA SEKOLAH DASAR DALAM PEMECAHAN MASALAH GEOMETRI: SEBUAH STUDI LITERATUR - Lestari, Dinar Dwi Putri; Naila, Ishmatun (universitas Ahmad Dahlan, 2021)
Spatial abilities fall into the category of essential subjects for elementary school students to master, especially mathematics. The fact that students' mathematical abilities, especially spatial abilities, are still relatively low is inevitable. One of the reasons for students' low mathematical ability is the abstract mathematical characteristics, for example, in geometry. This study aims to collect as much literature as possible to explore the study of elementary school students' spatial ability profile with content analysis techniques. The results of this study indicate that the students' low spatial abilities can be influenced by strategies and high-order thinking skills.